2021
DOI: 10.5551/jat.57737
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Cardio-Ankle Vascular Index (CAVI) with Biatrial Remodeling in Atrial Fibrillation

Abstract: Arterial stiffness results in elevated left ventricular filling pressure and can promote atrial remodeling due to chronic pressure overload. However, the impact of arterial stiffness on the process of atrial remodeling in association with atrial fibrillation (AF) has not been fully evaluated. Methods:We enrolled 237 consecutive patients diagnosed with AF who had undergone ablation; data from 213 patients were analyzed. Cardio-ankle vascular index (CAVI) was used as a marker of arterial stiffness. The left atri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
(38 reference statements)
1
12
1
Order By: Relevance
“…Several studies have described that the arterial stiffness determined by the CAVI is related to atrial remodeling. 14,15 The reason is because an increased arterial stiffness and atrial remodeling share common risk factors, such as the age, DM, hypertension, dyslipidemia, and obesity, and an increased arterial stiffness induces elevations in the left ventricular filling pressure, which can result in atrial remodeling due to a chronic pressure overload. 16 Atrial remodeling has been defined as a persistent change in the atrial size or function.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have described that the arterial stiffness determined by the CAVI is related to atrial remodeling. 14,15 The reason is because an increased arterial stiffness and atrial remodeling share common risk factors, such as the age, DM, hypertension, dyslipidemia, and obesity, and an increased arterial stiffness induces elevations in the left ventricular filling pressure, which can result in atrial remodeling due to a chronic pressure overload. 16 Atrial remodeling has been defined as a persistent change in the atrial size or function.…”
Section: Main Findingsmentioning
confidence: 99%
“…However, Nakamura et al reported that there was a strong correlation between the CAVI values during AF and those during sinus rhythm. 14 Therefore, the reproducibility of the CAVI during AF might be relatively high and useful for evaluating the arterial stiffness even in patients with non-PaAF.…”
Section: Limitationsmentioning
confidence: 99%
“…In this issue of the Journal of Atherosclerosis and Thrombosis, Nakamura et al examined the relationship between CAVI and atrial remodeling in association with AF in 213 consecutive patients with AF undergoing ablation 6) . Computed tomography was used to determine the atrial volume, and a threedimensional electromapping system was used to evaluate atrial electrical remodeling.…”
Section: See Article Vol 27: 000-000mentioning
confidence: 99%
“…The authors also noted several limitations of the study 6) . The observational nature precludes any causal inference.…”
mentioning
confidence: 98%
“…14 Several crosssectional studies have shown that CAVI reflects cardiac structural and functional changes associated with AF. 15,16 Furthermore, increased CAVI is significantly associated with AF prevalence even after adjusting CVD risks, 17 indicating the bidirectional interaction between systemic arterial stiffening and AF. However, the predictability of CAVI for the new-appearance of AF has not yet been explored, especially in general population receiving health screening.…”
Section: Introductionmentioning
confidence: 99%